Correction to: Human microbiota modulation via QseC sensor kinase mediated in the Escherichia coli O104:H4 outbreak strain infection in microbiome model (BMC Microbiology, (2021), 21, 1, (163), 10.1186/s12866-021-02220-3) - Ribeiro, Tamara Renata Machado [UNESP]; Salgaço, Mateus Kawata [UNESP]; Adorno, Maria Angela Tallarico; da Silva, Miriam Aparecida; Piazza, Roxane Maria Fontes; Sivieri, Katia [UNESP]; Moreira, Cristiano Gallina [UNESP] (Springer Nature, 2021)
Following the publication of the original article [1], we were notified that the captions for Figs. 2, 3 and 5 needed adjustments. Original captions: